Context- and Output Layer-Dependent Long-Term Ensemble Plasticity in a Sensory Circuit - Yamada, Yoshiyuki (Neuron, 2017)
Sensory information is translated into ensemble representations by various populations of projection neurons in brain circuits. The dynamics of ensemble representations formed by distinct channels of output neurons in diverse behavioral contexts remains largely unknown. We studied the two output neuron layers in the olfactory bulb (OB), mitral and tufted cells, using chronic two-photon calcium imaging in awake mice. Both output populations displayed similar odor response profiles. During passive sensory experience, both populations showed reorganization of ensemble odor representations yet stable pattern separation across days. Intriguingly, during active odor discrimination learning, mitral but not tufted cells exhibited improved pattern separation, although both populations showed reorganization of ensemble representations. An olfactory circuitry model suggests that cortical feedback on OB interneurons can trigger both forms of plasticity. In conclusion, we show that different OB output layers display unique context-dependent long-term ensemble plasticity, allowing parallel transfer of non-redundant sensory information to downstream centers. VIDEO ABSTRACT: